Pengaruh Kualitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, Dan Pengendalian Intern Terhadap Keterandalan Pelaporan Keuangan Pemerintah Daerah( Studi kasus di SKPD Kota Surakarta ) - Putra, Natalido Karunia; , Dr. Noer Sasongko SE.,Ak.,M.Si (2016)
The purpose of this study was to examine the influence of human resources, utilization of information technology and internal control of the reliability of financial reporting area. The object of this study are employees working at SKPD Surakarta, finance department, based on purposive sampling method, obtained a sample of 46 respondents. Data were collected using a questionnaire, after the data is collected and the data were analyzed using multiple regression analysis. The results showed that the human resources and internal controls affect the reliability of financial reporting areas, while the use of information technology does not affect the reliability of financial reporting area